(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to apply one of the techniques of management accounting, which is the Quality Function Deployment(QFD) on the Pepsi product in Baghdad Soft Drinks Company and to determine the technical requirements objectively that have been applied in practice in Baghdad Soft Drinks Company / a private shareholding company, as it focuses on meeting the quality requirements and achieving positive quality to provide a product It meets the requirements of current and future customers, hence the importance of research that indicates that the Quality Function Deployment(QFD) is a useful tool to develop the requirements of new products, being a design process driven by customers through their voices, and thus contribute to achieve a competitive advantage, Our research problem has emerged, which requires each economic entity to adopt the best technologies that enable it to compete and outperform its competitors in order to win the response of the customer’s voice because it is the focus of the production process and drive to achieve the appropriate quality and lower cost and rapid response to the markets in order to gain customer satisfaction.